Dinamika Populasi dan Identifikasi Bakteri pada Proses Dekomposisi Awal Campuran Lumpur Susu dan Jerami Padi dengan Perbedaan Nisbah C/N - Kurniawan, Endang; Badruzzaman, Deden Zamzam; Marlina, Eulis Tanti (Jurnal Teknologi Hasil Peternakan, 2023)
Milk sludge has the potential to be converted into compost with the addition of rice straw as a counterbalance in carbon and nitrogen content for a source of microorganism nutrition. Early decomposition is the highest phase of microorganism growth. Microorganisms that play a dominant role are bacteria. This study aims to determine the number, population dynamics, characteristics of bacteria in the initial decomposition process of a mixture of milk sludge and rice straw with differences in the ratio of C / N. The study was conducted for 7 days with experimental and descriptive methods with 3 treatments (P1 = C/N 25, P2 = C/N 27,5, and P3 = C/N 30) and random sampling by sampling. Data on the number of bacterial populations were analyzed using ANOVA while population dynamics and bacterial characteristics used descriptive methods. The number of bacterial populations of each treatment is not influenced by different C/N ratios and has a range of P1 ranging from 0,49 x 10 12 to 27,93 x 10 12 cfu/gram, P2 ranging from 0,39 x 10 12 to 19,32 x 10 12 cfu/gram, and P3 ranging from 0,95 x 10 12 to 10,55 x 10 12 cfu/gram. The population dynamics of bacteria are sigmoid and occur due to temperature fluctuations in the decomposition process. The macroscopic characteristics of each treatment have the same relative shape including filamentous, irregular, circular, rhizoid and white in color and differ on surface and edges. While the microscopic characteristics of bacteria are dominated by rod cell shapes and are gram-positive.